MÁRIA SZIKSZAI, Community Networks and Cultural Practices in Twentieth-Century Romania: Paper-Based Cultures in the Writings of a Catholic Priest - MITRULY, ÁRPÁD ( NYELV- ÉS IRODALOMTUDOMÁNYI KÖZLEMÉNYEK , 2026)
Author's coordinates: Babeș-Bolyai Tudományegyetem, Hungarológiai Doktori Iskola, Kolozsvár/Cluj-Napoca, Horea 31 Email: arpadmitruly@gmail.com Text Complet - PDF (Magyar)